First steps into the cloud and continuous delivery - Gerber, Anna (Software developer); Mayr, Alois (O'Reilly, 2018)
To remain competitive in today's digital world, large businesses need to move fast. That's why so many companies plan to shift from monolithic onsite architectures to applications designed solely to operate on cloud computing platforms. But how do companies successfully migrate toward cloud-native technologies and practices? This article examines challenges identified by respondents to the Cloud Platform Survey that businesses face as they take their first steps into the cloud. It also describes key best practices and enabling tools for continuous integration and delivery, automation, and monitoring.